Cell selection analysis in outdoor heterogeneous networks - Tongwei Qu; Dengkun Xiao; Dongkai Yang; Wei Jin; Yuan He (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
LTE-Advanced is one of the most candidate 4G technologies, and cell selection plays a crucial role in improving cell spectral efficiency. This paper is supported by performances comparisons and analysis between the new cell selection method and the conventional cell selection method, in order to explore cell selection efficiency in LTE-A heterogeneous systems.